Comparative response of direct seeded and transplanted maize (Zea mays L.) to nitrogen fertilization at Zanyokwe irrigation scheme, Eastern Cape, South Africa - M. Fanadzo; C. Chiduza; P. N. S Mnkeni (Global Journal of Food and Agribusiness Management, 2018)
Previous studies carried out in smallholder irrigation schemes in South Africa showed that bird damage to emerging seedlings reduced crop stand and yield of maize. Transplanting offered an opportunity to improve stand but there was no information on fertiliser management of transplants. An on-farm experiment was therefore conducted to compare the response to nitrogen (N) rate (60, 120, 180, 240 and 300 kg N ha-1) of direct seeded and transplanted maize. Transplanting resulted in a significantly higher crop stand of 96% compared to direct seeding, which achieved 78%. Transplanted maize had shortened growth duration in the field, reaching flowering stage 11 to 15 days earlier than direct seeded maize. At low N rates, transplants produced higher green cob weight, grain yield and longer cobs than direct seeded maize. The economically optimum N rates required to obtain marketable cobs were 149 and 98 kg ha-1, whilst those required for achieving optimum grain yields were estimated at 240 and 227 kg ha-1 with direct seeding and transplanting, respectively. The findings suggest that transplanted maize can be grown at lower N rates to achieve similar yield potentials as direct seeded maize, and that transplanting can help in improving crop stands in areas where bird damage on emerging seedlings is a problem.